(untitled) (MAUSAM, 1984)
Droughts, generally understood as a period of dryness due to lack of rain is inter preted variously depending on the normal climatic conditions, available water resources, agricultural practices and economic activities of the region. Depending on the purpose of study and basic criteria chosen, all the concepts and definitions regarding droughts may be classified as precipitation droughts, atmospheric droughts, agricultural droughts and hydrologic droughts. Most of the literature on droughts is based on the analysis of precipitation and temperature records -the statistical techniques are quantitative and often lack the physical basis while the non-statistical ones are empirical. On the other hand, Thornthwaite’s water budget method is quantitative and based on a sound and rational physical approach. According to this, drought cannot be defined in terms of rainfall deficiency alone, without taking into account the water need of the region and the role of soil moisture. In the present study, droughts during the period 1901-1975 over Tamil Nadu and vicinity have been analysed by the application of the water balance approach. Droughts, however, require extended periods of time to develop as they are usually the culmination of a set of weather sequences. Aridity, anomaly diagrams on a yearly basis have, therefore, been drawn which show annual fluctuation in aridity presumably caused by large-scale changes in general circulation of the atmosphere. With the annual patterns as a basis, drought spread diagrams on a monthly basis have been drawn to identify the ’cove’ areas and periods. After identifying the drought spells of various intensities and their spread, the cumulative effect of these water deficiencies in dry spells were assessed by employing the cumulative deviation technique. This method besides giving an objective assessment of drought severity, also indicates the beginning, duration and end of a drought spell- the components of a regular life cycle.